Ovinos : Bancos Germoplasma - ‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
Ovinos-Ganado ovino - Ovis aries